Pre-Service Elementary Teacher in Global Warming and Environmental Health Issue: Attitude in Natural Science Learning - Ilmi Zajuli Ichsan; Rika Sa'diyah; Nur Fadli Hazhar Fachrial; Ainur Rosyid; Rosa Susanti (Postgraduate, University of Mataram, 2022)
Pre-service elementary teachers’ attitude in supporting the achievement of the ecosystem and environmental balance is necessary to implement. Most global warming topic taught in natural science learning has yet to be based on environmental orientation. This research purpose was to analyze pre-service elementary teachers’ attitudes in preventing global warming and environmental health issue. The research uses a descriptive method with the data collection technique of the survey. The research samples include 239 students of the Department of Elementary Teacher Education in Jakarta, Bogor, Depok, Tangerang, Bekasi (Jabodetabek) area. These students are pre-service elementary teachers. Data analysis used is by comparing the average score of each item and indicator. The research result indicates that the average score for attitudes is 87.33 suggesting that the attitude score is relatively high. The attitudes, however, have not been fully implemented in the form of attitudes to prevent global warming and environmental health issue. Natural science learning plays a prominent role in providing understanding related to global warming. The research results also recommend the application of more applicable lecture activities to the pre-service elementary teachers to improve the pre-service teacher attitude in natural science learning. The research concludes that the score of the pre-service elementary teachers’ attitudes is within a high category